Co-application of molybdenum and zinc increases grain yield and photosynthetic efficiency of wheat leaves - Chunkui Liu; Chengxiao Hu; Qiling Tan; Xuecheng Sun; Songwei Wu; Xiaohu Zhao (Plant, Soil and Environment, 2019)
The effects of the co-application of molybdenum (Mo) and zinc (Zn) on winter wheat grain yield, leaf photosynthetic efficiency, and antioxidant activity were investigated using pot culture experiments with sandy soil. Four treatments were investigated, including a control (CK), 0.15 mg Mo/kg soil (Mo), 1 mg Zn/kg soil (Zn), and 0.15 mg Mo/kg + 1 mg Zn/kg soil (Mo + Zn). The results showed that the soil application of Mo and Mo + Zn increased the winter wheat grain yield, spike number, and thousand kernel weight, coupled with significant enhancement in nitrate reductase activity, chlorophyll a and chlorophyll a + b contents, as well as the photosynthetic rate of the leaves, which were also positively correlated with grain yield. Furthermore, the co-utilization of Zn and Mo + Zn significantly increased the activities of superoxide dismutase, catalase, and peroxidase in the leaves. The overall results indicate that the co-application of Mo and Zn can increase winter wheat grain yield by improving the leaf photosynthetic efficiency and antioxidant ability.